2017
DOI: 10.1055/s-0037-1603447
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Complications in Hepatobiliary Surgery

Abstract: Hepatobiliary surgery is a well-known risk factor for thrombotic complications but is also associated with substantial perioperative blood loss. Given the central role of the liver in hemostasis, hepatobiliary surgery is frequently accompanied by complex changes in the hemostatic system. Increasing knowledge of these changes has resulted in an improved understanding of the etiology of some of the hemostatic complications. In the early postoperative period a prolongation of conventional coagulation test times, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…With the developments in surgical technique and concept of perioperative management, the postoperative incidences of morbidity and mortality have greatly decreased; however, the condition is still not satisfactory, and the incidence of major complications after hepatopancreatobiliary surgery is still high [48][49][50]. The prevention and treatment of major complications have remained of paramount significance in improving the outcomes of patients, and the preoperative risk evaluation and clinical intervention are effective measures to prevent the occurrence of major complications.…”
Section: Discussionmentioning
confidence: 99%
“…With the developments in surgical technique and concept of perioperative management, the postoperative incidences of morbidity and mortality have greatly decreased; however, the condition is still not satisfactory, and the incidence of major complications after hepatopancreatobiliary surgery is still high [48][49][50]. The prevention and treatment of major complications have remained of paramount significance in improving the outcomes of patients, and the preoperative risk evaluation and clinical intervention are effective measures to prevent the occurrence of major complications.…”
Section: Discussionmentioning
confidence: 99%
“…In surgical procedures involving the liver, notably partial liver resections and liver transplantation, substantial perioperative changes in hemostatic components may occur. 31 These changes may occur in patients who had a normal preoperative hemostatic status, such as in the noncirrhotic patient undergoing partial hepatectomy for metastatic disease or the patient with a disorder such as familial amyloid polyneuropathy requiring a liver transplant. Perioperative hemostatic changes may also occur in patients who had cirrhosis-related hemostatic changes preoperatively.…”
Section: Platelets and Liver Surgery: Alterations And Consequences Fomentioning
confidence: 99%
“…As a result, these patients have often been considered to be at an increased risk of postoperative bleeding, leading to frequent administration of blood components, and delayed thromboprophylaxis, despite evidence that postoperative VTE is more common than postoperative bleeding in this setting. 45 VETs have been used to assess whether or not a true coagulopathy exists in this setting. In a study of 40 patients undergoing hepatectomy, the authors showed that despite significant elevations in INR/PT postoperatively, TEG parameters suggested an initial hypercoagulable postoperative state, which quickly transitioned back to normal.…”
Section: Hepatectomymentioning
confidence: 99%